Effectiveness of Replacing Rice Bran with Palm Oil Processing Solid by-products (Solid) on the Performance of Kaur Cattle - Jarmuji, Jarmuji; Aziz, Arif Rahman (Universitas Bengkulu, 2025)
Sakura Block Plus is a feed supplement designed to enhance cattle performance, with rice bran accounting for 22% of its total ingredients. However, due to the increasing scarcity and rising prices of rice bran, palm oil processing solid by-products offer a potential alternative. This study aimed to assess the effect of Sakura Block Plus supplemented with solid at different levels as a substitute for rice bran on dry matter intake and body weight gain in Kaur cows fed a natural grass diet. A Latin Square Design (LSD) was employed, involving four treatments and four replications. The treatments consisted of wild grass plus a sakura block, with 5.5% (P1), 11% (P2), 16.5% (P3), and 22% (P4) of the solid as rice bran replacement. The results indicated that replacing rice bran with solid up to 22% did not significantly affect dry matter intake (P>0.05). Still, there was a trend toward increased body weight gain at the highest solid level. Dry matter intake averaged 7.22-7.96 kg/head/day (2.80-3.06% of body weight), while body weight gain ranged from 0.41-0.52 kg/head/day. These findings suggest that solid can replace up to 100% of rice bran in sakura block plus formulations without adversely affecting cattle performance.